Analisis Kekuatan Tarik Pada Jenis Sambungan Hybrid Tipe Lap Joint Komposit Serat Widuri - Hule, Esau; Pell, Yeremias M.; Maliwemu, Erich U.K. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2023)
This research was conducted to analyze the strength of this hybrid lap joint type of thistle fiber composite due to tensile loading. The hybrid connection types used are bolted and adhesive connections. Thistle fiber composite has a volume fraction of 30 % and fiber length is 5 mm. To produce a bolted connection, the composite is perforated by drilling. Then it is connected with adhesive to become a hybrid connection. Specimen sizes follow ASTM D5961 standards. In addition to the type of hybrid connection above, the distance of the holes in this connection also varies. From the tensile test results obtained at a hole spacing of 16 mm has a stress of 5.9 MPa, a strain of 0.088 % and a modulus of elasticity of 7.959 GPa. The composite with a hole spacing of 36 mm has a stress of 7.2 MPa, a strain of 0.126 % and a modulus of elasticity of 6.068 GPa. The composite with a hole spacing of 56 mm has a stress of 5.6 MPa, a strain of 0.064 %, and a modulus of elasticity of 10.136 GPa.